Reform Within Islam - Bedri Gencer (International Institute of Islamic Thought, 1998)
When the western influence or civilization came to impinge upon the Muslim world in the late eighteenth century, a profound process of transformation began in Muslim thought. There had been so many encounters between the West and the East, or in other words, between Islam and Christianity over centuries in various ways and on different levels. However, this was a novel phenomenon, without antecedents, resulting from "the technical age" and accordingly from a state of comparative superiority among nations placing them inexorably in an objective hierarchy in terms of their use of the possibilities of this age. (The term "technical age" is used here as defined by Marshall G.S. Hodgson in The Venture of Islam as a universal human development, contrary to the term "modem age," which implies western superiority.) Having lost the sense of absolute superiority provided by their faith, Muslims had come to feel themselves more vulnerable to the Western challenge than ever. Quite naturally this led Muslim thinkers to question their thought, religion, and civilization in comparison with those of the West Few if any thinkers, like the architect of the Majalla, Ahmed Cevdet Pa????a. the foremost intellectual figure in modem times, in whom the authentic 'alim tradition was embodied, remained bound to the idio-sources and possibilities of Islamic thought in coping with the Western challenge to the bitter end. The bulk of the Muslim intelligentsia and 'ulama, far from possessing a staunch, implicit faith in the self-sufficiency of Islamic legacy, as Ahmed Cevdet Pa§a has, felt themselves as bound to compromise with western thought in some way or other. Then a new way of thinking on the part of Muslim thinkers "Islamic modernism" came into being. Seen in this light, Islamic modernism marks a decisive rupture in the history of Islamic thought in that it represents an attempt at renewal from outside, as opposed to the ihya or tajdid tradition codified by the Prophet himself, which ...